Key elements of interface design for washing machine based on user's preferences : a case study in Malaysia - Abushammala, Sakher J. I. (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Washing machine plays an essential and pivotal role in our daily modern lives. Washing machine have great impact generally, socially and economically on Malaysian people. Washing machine is one of the great inventions of the industrial revolution. It was named 12th most important invention by Tesco Mobile UK. Socially it contributed in our daily washing routines saving time and effort. It promoted cleanliness and hygiene and has profound impact transforming women's lives enabling them entering the workforce. Economically washing machine is on top three most important households in Malaysia according to national Census 2010. Washing machine design trends have been rapidly changing since the beginning of its invention that support assorted washing techniques and methods. As a result, washing machine interface design become more complex, difficult to operate, hard to understand. Washing machine interface design become problematic with big many modes, features added to the panel or dashboard. Many features are unnecessary and create confusion between users. The interface design can be more user friendly and easier to understand and operate, needed to be simplified. Interface design principles were gathered through literature review based on interface design experts' key elements of interface design as a result key element are 1) functions, 2) design, 3) operation, 4) design approach. A survey has been done on a sample of 300 washing machine users located in Kuala Lumpur using data collection, key elements of interface were identified as a result based on 1) functions, 2) user preferences. Line up study of 14 current washing machine interface design in the market has been done to observe, analyze, compare between existing interface designs to come up with design key elements as a result. Based on 1) design, 2) functions, 3) operation. Over all findings shows that there are key elements that required for washing machine interface design resulting in making interface design more user friendly with primary functions and tasks based on Malaysian user's preferences. A proposed interface design is validated using task analysis approach by industrial designer experts. Research have important value in adding new information about interface design key elements for washing machine based on user's preferences and in relation to interface design principles by experts. Keywords: Washing machine, Interface Design, Functions, Human centered design, Interface principles.